An Inventory Control System to Minimize the Cost of Disposing of Expired Goods in Multi Indah Store - Arisandy, Desi; Rudi; Caroline; Reid; Alvin (Talenta Publisher, 2023)
Multi Indah store is a small business engaged in the sale of shoe raw materials. The customer is a shoemaker. The problem faced by stores today is the process of sorting the shelf life which takes quite a long time so that it has an impact on the slow delivery of goods to customers. The development of an inventory control system using the RAD methodology is a solution offered to stores. The results of the system test found that the sorting process is faster and can help control the amount of inventory, service life, and items that are nearing expiration can be known quickly by shop owners through reports presented by the system.